An unusual translocation, t(1;11)(q21;q23), in a case of chronic myeloid leukemia with a cryptic Philadelphia chromosome - Gutierrez, Leandro German (2017)
Chronic myeloid leukemia is characterized by the translocation t(9;22)(q34;q11) (Philadelphia chromosome). Although it is not frequent, additional chromosome abnormalities can be detected at diagnosis and some of them have been associated with adverse cytogenetic and molecular outcome. We report a case of Chronic myeloid leukemia presenting the translocation t(1;11)(q21;q23) and a cryptic Philadelphia chromosome. The presence of additional chromosome abnormalities could generate greater genetic instability, promoting the emergence of further alterations. Our findings suggest that t(1;11)(q21;q23) avoided good response to tyrosine kinase inhibitors therapy. The patient evolves with primary resistance and subsequently at the recent control the T315I mutation was detected.